2019
DOI: 10.3390/cells9010100
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Network of Forkhead Family of Transcription Factors (FOXO) in Dietary Restriction

Abstract: Dietary restriction (DR), which is defined as a reduction of particular or total nutrient intake without causing malnutrition, has been proved to be a robust way to extend both lifespan and health-span in various species from yeast to mammal. However, the molecular mechanisms by which DR confers benefits on longevity were not yet fully elucidated. The forkhead box O transcription factors (FOXOs), identified as downstream regulators of the insulin/IGF-1 signaling pathway, control the expression of many genes re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 149 publications
(185 reference statements)
0
28
0
1
Order By: Relevance
“…In RPE cells, stimulation of autophagy by rapamycin was found to protect ARPE-19 cells from a lethal dose of H 2 O 2 [ 7 ]. Despite being a potent autophagy activator, many lines of evidences have shown that rapamycin has many adverse effects, such as diabetic-like symptoms, gastrointestinal disorders, and increased risk of infection [ 37 , 38 ]. Therefore, it is important to search for other alternatives with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…In RPE cells, stimulation of autophagy by rapamycin was found to protect ARPE-19 cells from a lethal dose of H 2 O 2 [ 7 ]. Despite being a potent autophagy activator, many lines of evidences have shown that rapamycin has many adverse effects, such as diabetic-like symptoms, gastrointestinal disorders, and increased risk of infection [ 37 , 38 ]. Therefore, it is important to search for other alternatives with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Human studies support these findings by revealing greater longevity in people with smaller body size (Chmielewski 2016;Samaras 2014;Samaras 2013). Downstream of GH-IGF1, both mTOR (Blagosklonny 2013a;Blagosklonny 2013b;Papadopoli et al 2019;Wilkinson et al 2012) and FOXO (Daitoku and Fukamizu 2007;Jiang et al 2019) cascades are considered as central mechanisms of longevity regulation.…”
Section: Gh/igf/mtor and Gh/igf/foxo Signaling Cascadesmentioning
confidence: 82%
“…In fact, of the > 40 genetic mutations that have been reported to extend lifespan in the mouse and the rat models, approximately one third of them are involved in GH and IIS [164]. Because CR reduces GH and IIS [164], it is generally accepted that CR extends lifespan by limiting GH/IIS signaling and subsequently expressing pro-longevity genes by activating FOXO transcription factors [165]. To date, there are mixed results reported for the question of whether the IIS-FOXO signaling cascade is responsible for CR-mediated lifespan extension.…”
Section: Iis-foxo Signalingmentioning
confidence: 99%